Design of a Model Predictive Control for Speed Control of a Motor Drive System in an Electric Oil Palm Cutter - Ferdiansyah, Indra; Sholihah, Fifi Hesty; Prabowo, Gigih; Purwanto, Era; Hairulnizam, Hairul Faizi (Agroindustrial Technology Journal, 2025)
This study presents the design of a speed control system for a Motor Drive Permanent Magnet Synchronous Motor (MDPMSM) to achieve a faster and more stable dynamic response in an electric oil palm cutter, supporting the harvesting process of oil palm fruit. Conventional control methods such as Proportional-Integral (PI) controllers, which are commonly applied, still face challenges in parameter tuning and exhibit high sensitivity to speed variations in cutting operations. To overcome these limitations, this research proposes a Model Predictive Control (MPC)-based speed regulation system integrated into a Field-Oriented Control (FOC) structure for a encoderless MDPMSM. The mathematical model of the motor serves as the foundation for designing the predictive algorithm, which can estimate motor speed behavior in real time. Performance evaluation was conducted through simulations under step-response conditions involving sudden speed changes, as well as ramp-response conditions. The simulation results were compared with those of the PI controller to assess the system’s ability in achieving steady-state time, overshoot, and undershoot. The results demonstrate that the MPC-based controller significantly enhances system performance, achieving up to a 60% reduction in settling time, an 84% decrease in overshoot, and a 58% improvement in recovery capability. Moreover, under ramp-response testing, the MPC-based system exhibited a more linear and responsive speed-tracking performance. Therefore, the proposed MPC control design proves to be effective in improving the accuracy and stability of encoderless MDPMSM speed control systems and serves as a reliable alternative for high-precision motor drive control applications, particularly in electric oil palm cutting systems.